2006
DOI: 10.1038/emm.2006.50
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JNK-initiated p53 accumulation and phosphorylation of p53 in pseudolaric acid B induced cell death

Abstract: A terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) assay was used to determine that apoptosis causes HeLa cell death induced by pseudolaric acid B. The c-Jun N-terminal kinase (JNK) inhibitor SP600125 decreased p53 protein expression during exposure to pseudolaric acid B. SP600125 decreased the phosphorylation of p53 during pseudolaric acid B exposure, indicating that JNK mediates phosphorylation of p53 during the response to pseudolaric acid B. SP600125 reversed pseudolaric acid B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Bax and p53 was upregulated by proton beam (data not shown), sug-gesting that p53 increased cell death through the transcription-dependent apoptotic mechanism in LLC cells. Usually p53 activates caspases by the mitochondrial pathways (Schuler and Green, 2001;Kadenbach et al, 2004;Gong et al, 2006) or alternatively by generation of ROS (Polyak et al, 1997;Li et al, 1999). From our results, proton beam activates caspase-3 as well as increased oxidative stress.…”
Section: Discussionmentioning
confidence: 53%
“…Bax and p53 was upregulated by proton beam (data not shown), sug-gesting that p53 increased cell death through the transcription-dependent apoptotic mechanism in LLC cells. Usually p53 activates caspases by the mitochondrial pathways (Schuler and Green, 2001;Kadenbach et al, 2004;Gong et al, 2006) or alternatively by generation of ROS (Polyak et al, 1997;Li et al, 1999). From our results, proton beam activates caspase-3 as well as increased oxidative stress.…”
Section: Discussionmentioning
confidence: 53%
“…PAB exerts potent antifungal, antimicrobial [1] , antifertility [2,3] , and cytotoxic activity in vitro [4] , and the mechanisms of PAB-induced cell death in human myelocytic leukemia K562, human cervical carcinoma HeLa, and human melanoma A375-S2 in vitro have been reported [5][6][7] . However, the mechanism of PAB-induced cell death in human breast cancer MCF-7 is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…PAB is a diterpene acid isolated from the root and trunk bark of Pseudolarix kaempferi and possesses multiple biological and pharmacological activities, including antifungal, antimicrobial, antifertility and antiangiogenic properties (10)(11)(12)(13)(14)(15). It has been previously confirmed that PAB exhibits an antitumor effect by inducing apoptosis in various types of cancer (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Apoptosis is important in homeostasis maintenance through a balance between cell proliferation and cell death (28).…”
Section: Discussionmentioning
confidence: 99%
“…In human HeLa cervical carcinoma cells, PAB promotes apoptosis via activating c-Jun N-terminal kinases (JNK), protein kinase C (PKC) and caspase-3, downregulating extracellular signal-regulated kinases (ERK) and Bcl-2 as well as upregulates the P53 and Bax proteins (16,17). In human melanoma A375-S2 cells, PAB inhibits proliferation and induces apoptosis by arresting the cell cycle at the G2/M checkpoint, upregulating P53 and Bax levels and downregulating expression of Bcl-2 and Bcl-xl proteins (18).…”
Section: Introductionmentioning
confidence: 99%